Channel Youtube Al-Fikrah Dalam Membangun Relasi Santri Alumni Pesantren Mambaus Sholihin Manyar gresik - Rifky Bachtiar; Aflachal Muthowah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah bekerjasama dengan LP2M Institut Pesantren Sunan Drajat Lamongan, 2023)
New media media Youtube channel which broadcasts several pesantren shows. The media is an alternative media for alumni who are not domiciled in the pesantren environment, to treat the longing for alumni and caregivers, the media is a bridge between caregivers and alumni. The media broadcasts book studies and tausiyah, which are two media programs to carry out the mandate of caregivers, namely tafaquh fiddin. The problems in this research are: (1) What is the process for showing Al-fikrah Youtube channel? (2) What are the weaknesses and strengths in building Santri alumni relations? This study used the triagulation method, namely data analysis before going to the field, data analysis while in the field (miles and Huberman method), data reduction. In this method, the author was able to find the results of the research, which is a process of silaturrahmi alumni with caregivers through the Al-fikrah YouTube media. From these results, the writer can find data in the form of facts about the alumni's relationship with caregivers through the media intermediary. This channel is to continue the relay of Al-fikrah magazine which is stagnant and considered inefficient. Through this broadcast, alumni from various regions have a great opportunity to continue participating in book studies and tausyiah. The results of this study indicate that building alumni relations from the Al-fikrah Youtube channel is very necessary considering the alumni areas that are far apart and busy with activities. The media is Islamic boarding school education and also tausyiah caregivers as well as international guests who wish to share knowledge with the Islamic boarding school regarding this phenomenon. It is hoped that the relationship between alumni and pesantren is maintained.